Promoting access to medical technologies and innovation : intersections between public health, intellectual property and trade (WHO GenevaCH, 2012)
Presents the general background to health policy relating to medical technologies, sets out the distinct roles and mandates of the three cooperating agencies and outlines the global disease burden that defines the essential challenge for health policy. Outlines the elements of the international framework - health policy, IP and trade policy - laying an integrated basis for the following more detailed analysis of the innovation and access dimensions. Provides a more detailed overview of policy issues concerning the innovatio dimension of medical technologies.
Keywords: PUBLIC HEALTH